2016
DOI: 10.1038/ncomms13484
|View full text |Cite
|
Sign up to set email alerts
|

Polarization curling and flux closures in multiferroic tunnel junctions

Abstract: Formation of domain walls in ferroelectrics is not energetically favourable in low-dimensional systems. Instead, vortex-type structures are formed that are driven by depolarization fields occurring in such systems. Consequently, polarization vortices have only been experimentally found in systems in which these fields are deliberately maximized, that is, in films between insulating layers. As such configurations are devoid of screening charges provided by metal electrodes, commonly used in electronic devices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 34 publications
(35 reference statements)
3
56
1
Order By: Relevance
“…In comparison with the recently increasing number of experimental reports on the preparation and characterization of magnetic skyrmions [3][4][5][6][7], there are only limited works in the literature on experimental characterizations of complex and nontrivial configurations of dipoles in ferroelectrics [8,21,30]. In the present study, we report on topological defects with distinct and novel configurations of electric dipoles in epitaxial multilayer films of PTO/STO.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In comparison with the recently increasing number of experimental reports on the preparation and characterization of magnetic skyrmions [3][4][5][6][7], there are only limited works in the literature on experimental characterizations of complex and nontrivial configurations of dipoles in ferroelectrics [8,21,30]. In the present study, we report on topological defects with distinct and novel configurations of electric dipoles in epitaxial multilayer films of PTO/STO.…”
mentioning
confidence: 86%
“…In ferroelectrics, physical properties and structures of various DWs have been studied theoretically [14][15][16][17] and experimentally [18][19][20][21][22][23]. It was found that the DWs possess different properties from that of the domains, depending on details of the wall structure [24][25][26], and thus have been considered as functional elements in future electronics [27].…”
mentioning
confidence: 99%
“…Besides, the edge structure is the typical characteristics of perovskite oxides nanostructures395051, while ferroelectric nanodots with similar round corner morphology have also be fabricated experimentally38. It is also worth to mention that the vortex-type polarization has been observed directly in low-dimensional systems5253. Thus, the characteristics of the models are realistic and it is highly possible to realize low-dimensional multiferroics experimentally as proposed here.…”
Section: Resultsmentioning
confidence: 73%
“…Topological structures (or defects) in ferroic materials, such as skyrmions, vortices, flux closures, incommensurate curl domains, and bubble domains, have recently attracted attention due to their emergent nature. They can display large current‐induced spin‐orbit torques, giant electromechanical response, enhanced or ballistic electron transport, chirality or colossal optical coefficients, to name just a few of their exciting properties.…”
Section: Introductionmentioning
confidence: 99%